Identifikasi Luasan Banjir Rob di Kota Semarang Pada Tanggal 24 Mei 2022 Menggunakan Citra Landsat - Andi Nur Rahman; Nia Kurniadin; Romansah Wumu; Shabri Indra Suryalfihra (Journal of Geomatics Engineering, Technology, and Science, 2023)
Tidal floods are floods that occur as a result of sea tides that inundate areas that have a lower elevation than sea level. The occurrence of tidal floods is due to sea level rise caused by tides, external forces such as water, wind, or swell (waves caused from a long distance), and storms which are natural phenomena that often occur at sea. A tidal flood in Semarang City on May 23, 2022, occurred with a height of 1.5 meters, occurred in the Tanjung Emas Port area. This tidal flood became the most severe flood in 2022. The utilization of remote sensing technology by using Landsat satellite imagery can be maximized to obtain information about tidal flood events that occurred in the city of Semarang. The purpose of this study was to find out how to identify the area of flooding using Landsat 8 and Landsat 9 imagery using the NDWI method and to determine the extent of the tidal flood that occurred on May 24, 2022, by comparing the wettability values of satellite imagery before and after the tidal flood. The results obtained are in the form of changes in the area of water bodies due to tidal flooding on the north coast of Semarang City in the Tugu sub-district 39.982 Ha; West Semarang 16.765 Ha; North Semarang 5.174 Ha; East Semarang 0.104 Ha; and Genuk 33.393 Ha.